Free radicals and scavenging enzymes in chronic tonsillitis - Kaygusuz, I; Ilhan, N; Karlidag, T; Keles, E; Yalçin, S; Çetiner, H (Wiley, 2003)
OBJECTIVE: This study aimed to define the relationship between chronic tonsillitis and levels of malondialdehyde and superoxide dismutase in free radical and antioxidant forms. It is suggested that free oxygen radicals may play a role in chronic tonsillitis. MATERIALS AND METHODS: One hundred twenty-four patients were enrolled in the study. Tonsillectomy was performed via the usual dissection-snare method. Venous blood was taken preoperatively and at 2 weeks postoperatively. Blood samples and tonsil specimens were evaluated for malondialdehyde and superoxide dismutase analysis. RESULTS: The levels of malondialdehyde and superoxide dismutase in plasma were compared preoperatively and postoperatively, and there were statistically significant differences between these levels (P < 0.05). In contrast, the levels of malondialdehyde and superoxide dismutase in tonsil tissue were not correlated with the plasma levels of malondialdehyde and superoxide dismutase in pretonsillectomy and posttonsillectomy terms (P > 0.05). CONCLUSION: The presence of malondialdehyde and superoxide dismutase in plasma and tonsil tissue reinforces the involvement of oxidative stress in the pathophysiology of chronic tonsillitis.
Keywords: Lipid Peroxides; Antioxidants; Injury; Damage; Assay